Catalog and Regional Budget Politics: Transparency and Accountability in Bungo Regency 2023 - Mulia Jaya; Siti Maryam; Agussalim (Jurnal Ragam Pengabdian, 2026)
This study aims to analyze the implementation of e-catalog in enhancing transparency of regional government spending, identify various inhibiting factors, and formulate optimization strategies within the General Affairs Section of the Bungo Regency Regional Secretariat in 2023. The research employs a descriptive qualitative approach through observation, documentation, and in-depth interviews, utilizing the interactive data analysis model of Miles, Huberman, and Saldana. Findings reveal that e-catalog significantly contributes to budget transparency by providing open procurement information, facilitating easy access to supplier data, and establishing digital audit trails that bolster accountability. However, its implementation remains suboptimal due to system disruptions, limited information technology infrastructure, low local supplier participation, and gaps in procurement personnel competencies. The regional government has implemented several improvement measures, including human resource capacity building, enhancement of IT facilities, socialization of LKPP regulations, development of digital-based procurement standard operating procedures, and strengthening of internal oversight mechanisms. This research affirms that e-catalog utilization serves as a strategic instrument for achieving more transparent, accountable, and efficient procurement governance at the local government level.